‘Clutch-the-ear’ and get enrolled: the antagonistic intrusion of indigenous knowledge systems to the detriment of contemporary educational developments - Zimano, Felistas R.; Matsaure, Keresencia; Chilunjika, Alouis (AOSIS, 2022)
Background: The use of non-conventional methods of measurement is a long-established practice in most societies. Aim: To investigate the effectiveness of non-conventional methods of measurement in the placement of children in schools in general and the ‘clutch-the-ear’ and get enrolled age measurement practice in particular. To expose the shortfalls of a classroom set-up in which age-for-grade enrolment is distorted. Setting: Zimbabwe. Methods: Literature review and researchers experiences. Results: The use of non-conventional methods has both pros and cons. The practice can be hailed for showing the indigenous knowledge systems as giving, to an extent, transparent and accurate maturity prediction ways that require preservation. However, it works perfectly for people of average height while prejudicing the outliers. The immediate conspicuous consequence is the late enrolment of the affected. In the case of the ‘clutch-the-ear’ and get enrolled measure, findings are discussed below. Conclusion: The use of non-conventional methods of age measurement unobtrusively upsets education quality through facilitating stereotyping, discrimination and age-heterogeneous classes. Researchers propose a ‘backward-integration-enrolment’ strategy; getting into communities to enrol not to wait for the community to bring children to school.